The Implementation of The Merdeka Curriculum in Learning English in Senior High School: Case Study - Tiara Vinnilarika Sari; Muamaroh (Universitas Cokroaminoto Palopo, 2024)
This study aimed to focus on the implementation of the Merdeka Curriculum in Learning English in Senior High School. The participants of this study were three English teachers at one of the Senior High School in Surakarta, Central Java, Indonesia. The study used a case study design with descriptive analysis. The instruments to collect data using interviews, observations, and documents. The data were analyzed qualitatively. The findings of this research reveal that teachers used three techniques in implementing the Merdeka Curriculum in the classroom such as CERIA, Quiz, and Jigsaw. Furthermore, this research also found materials used were textbooks and e-books sourced from the Ministry of Education and Culture Indonesia. Meanwhile, the learning media used by teachers are handphones and social media platforms such as Google forms, Duolingo, and WhatsApp groups. Teacher evaluations used formative and summative assessment.